PUBLICATIONS OF THE WEEK. (Bookseller, 2004)
This article presents a list of various books. Some of the books are, "Agency Uncovered: Archaelogical Perspectives on Social Agency, Power and Being Human," edited by Andrew Gardner, "Facets of South Indian Art and Architecture," by R. Nagaswamy, "Spatula: How Drawing Changed the World," by Gordon Shrigley, "Comics Journal Library, The: Drawing the Line," edited by Milo George, "Lake Artists Society: A Centenary Celebration Book — A History and Reference to the First 100 Years," by Jane Renouf.